Integrative taxonomy identifies two new tardigrade species (Eutardigrada: Macrobiotidae) from Greenland - Stec, Daniel; Tumanov, Denis T.; Kristensen, Reinhardt Møbjerg (European Journal of Taxonomy, 2020)
In this paper we describe Macrobiotus engbergi sp. nov. and Tenuibiotus zandrae sp. nov. from Greenland. Our study has involved both classical taxonomic methods, which include morphological and morphometric analyses conducted with the use of light and scanning electron microscopy, and genetic analysis based on four molecular markers (three nuclear: 18S rRNA, 28S rRNA, ITS-2, and one mitochondrial: COI). Moreover, we re-examined the type series of Tenuibiotus voronkovi (Tumanov, 2007) as well as the original sample where the species was found and we provide new morphological data from light and scanning electron microscopy which enabled us to amend its description. Finally, we also analysed slides with animals and egg of two populations from Nordaustlandet and Edgeøya (archipelago of Svalbard, Norway) designated as T. voronkovi within its recent redescription. The results and comparisons presented in our study question the validity of this designation.